Thermodegradation of medium-chain-length poly (3 hydroxyalkanoates), and assessment of the biopolyesters and oligoesters as plasticizer for poly(vinyl chloride) / Sin Mei Chan - Sin, Mei Chan (2012)
Medium-chain-length poly(3-hydroxyalkanoates) (mcl-PHA) are natural polyesters of hydroxyl fatty acids, composed of monomers with 6 to 14 carbon atoms length. These biopolyesters are primarily synthesized by fluorescent pseudomonads under nutrient imbalance, as carbon and energy storage compounds. In this study, mcl-PHA were produced by Pseudomonas putida PGA1 using oleic acid (OA) and saponified palm kernel oil (SPKO) as carbon source in shake flasks and fed-batch fermentations. From thermogravimetric analysis (TGA), the mcl-PHA derived from oleic acid (PHAOA) showed a drastic decomposition at temperature above 183ºC, while mcl-PHA derived from saponified palm kernel oil (PHASPKO) above 196ºC. Therefore thermal degradation of the PHAOA was carried out at temperatures of 160°C, 170°C and 180°C; whereas thermal degradation for the PHASPKO was performed at temperatures of 160°C, 170°C, 180˚C and 190°C, respectively. Changes in the polymer structures and properties before and after thermal treatments were studied by TGA, Differential Scanning Calorimetry (DSC), Gel Permeation Chromatography (GPC), Gas Chromatography (GC), Fourier Transform Infrared (FTIR) Spectroscopy, 400-MHz Proton Nuclear Magnetic Resonance (1H-NMR) Spectroscopy, and end group analysis.